Hubungan Tipe Strategi Bisnis dan Strategi Pemasaran dalam Menciptakan Keunggulan Bersaing Perusahaan dengan Menggunakan Manajemen Tenaga Penjual - Herlina . (Universitas Kristen Maranatha, 2006)
Competition is important for all company because it is can influence company’s success and failure. The company must have competitive advantage to reach superior performance. So that, the combination of business strategy in marketing and selling activities with human resource management (sales force) activities can produce competitive advantage to increase optimal result for long term.